Integration of Moral Hadith in Local Community Traditions: A Case Study of the Erau Tradition of Kutai Kartanegara - R. Rezeki Alam; Tajul Arifin (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
This study aims to explore moral values within the local Kutai tradition, specifically through a Hadith study examining the Erau Tradition in Kutai Kartanegara, East Kalimantan. The Erau tradition, as part of local culture, embodies values of character and ethics that align with Islamic teachings, particularly regarding solidarity, equality, and respect. This research employs a library research method with a descriptive qualitative approach, gathering data from various scientific articles, journals, and other literary sources. The findings reveal strong Islamic moral values within the practice of the Erau Tradition, such as religiosity, social ethics, and mutual respect. These results indicate that local traditions can serve as a medium to reinforce Islamic values, particularly in moral education and character development. Thus, this study is expected to provide deeper insights into the relationship between local culture and Islamic values and to enrich local wisdom-based educational approaches.